Ottoman Photography of the Late Nineteenth Century: An 'Innocent' Modernism? - Shaw, Wendy M. K. (History of photography, 2009)
Photography reached the Ottoman Empire soon after its invention, at about the time that painting began to be practised there as part of a broader project of assimilating aspects of European culture. This was in marked contrast to the situation in Europe, where photography had to contend with visual traditions from which it adopted pictorial conventions and subject matter. Instead of supplanting existing traditions of realistic visual representation, photography in the Ottoman Empire served as a discrete source of inspiration. This paper examines how this inversion of European experience within the Ottoman Empire provides an alternative to dominant narratives of photographic history. If one of the salient characteristics of modernist movements in Western art is their ability to break with tradition, then the adoption of Western practices of representation by artists within the Ottoman Empire may be viewed as a radical modernist success.